2020
DOI: 10.3390/atmos11101105
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bioaerosols in Selected Rooms of Two Schools and Antibiotic Resistance of Isolated Staphylococcal Strains (Bydgoszcz, Poland): A Case Study

Abstract: The present study is aimed at evaluating microbiological air pollution in libraries, cafeterias and selected classrooms of two schools in Bydgoszcz city, northern Poland and determining the antibiotic resistance of Staphylococcal strains isolated from the indoor air. One of the investigated schools (School A) is located in the very center of the city, in the vicinity of a park, among old houses and stone-lined streets, while the other (School B), among modern residential buildings, close to a street with heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
3
7
0
Order By: Relevance
“…9 Future perspectives Some of the work that could improve in the future is to standardise the sampling procedures, especially air sampling procedures as, there are no widely accepted methodologies for its measurement. Therefore, there is a need to investigate the potential of passive (based on spore sedimentation; expressed in CFU/m 2 /h) and active (based on vacuum pumps sucking air; expressed in CFU/m 3 ) air sampling strategies to explain visible mold, and understand how room characteristics of a museum or a film archive correlate with the obtained readings [161][162][163][164][165].…”
Section: Prevention and Controlmentioning
confidence: 99%
“…9 Future perspectives Some of the work that could improve in the future is to standardise the sampling procedures, especially air sampling procedures as, there are no widely accepted methodologies for its measurement. Therefore, there is a need to investigate the potential of passive (based on spore sedimentation; expressed in CFU/m 2 /h) and active (based on vacuum pumps sucking air; expressed in CFU/m 3 ) air sampling strategies to explain visible mold, and understand how room characteristics of a museum or a film archive correlate with the obtained readings [161][162][163][164][165].…”
Section: Prevention and Controlmentioning
confidence: 99%
“…The analyses showed the degree of air quality improvement (smaller CO 2 concentration) depended on the cubic area of the room. Małecka-Adamowicz et al [64] concluded the same thing regarding bio-aerosols. Larger per child cubic areas led to slower CO 2 concentration increases.…”
Section: Discussionmentioning
confidence: 79%
“…Filters applied in ventilation units are limited to pollution existing in the external environment (dusts, PM 10 , PM 5 , PM 2.5 ). Air quality improvement due to dust control should also improve the micro-biological situation of air, because dusts carry bacteria and fungi, including pathogens as noted by Małecka-Adamowicz et al [64]. It is also worth noting the suggestions of Bryzel et al [6] that air purification in the room is ineffective and should be purified before being delivered inside.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of staphylococci indicates the possible inherence of pathogenic microorganisms, in which antibiotic resistance has been observed with increasing frequency over the past several decades (Małecka-Adamowicz et al 2020 ). In this study Staphylococcus succinus was the most numerous staphylococcal species (approx.…”
Section: Discussionmentioning
confidence: 99%